A novel conductometric creatinine biosensor based on solid-state contact ammonium sensitive PVC-NH2 membrane - Isildak, Ibrahim; Cubuk, Osman; Altikatoglu, Melda; Yolcu, Murat; Erci, Vildan; Tinkilic, Nihat (ELSEVIER SCIENCE BV, 2012)
A novel, highly sensitive and stable conductometric biosensor for creatinine determination is developed. The biosensor is based on solid-state contact ammonium-sensitive sensor. Creatininase is chemically immobilized on the surface of the solid-state contact ammonium-sensitive membrane via glutaraldehyde covalent attachment method. The developed conductometric creatinine biosensors demonstrate high sensitivity and short response time toward creatinine. The detection limit of the biosensor was about 2 x 10(-6) M and the response time was shorter than 10s in phophate buffer solution at pH 7.20. The linear dynamic range of the biosensor was between 1 x 10(-1) and 9 x 10(-6) M creatinine concentration in phosphate buffer solution at pH 7.20. The biosensor exhibited good operational and storage stability for at least 4 weeks kept in dry at 4-6 degrees C. It had a reproducible and stable response during continuous work at least for 10 h with the relative standard deviation of 0.5% (n = 48) for creatinine of 1 x 10(-3) M in phosphate buffer solution. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Conductometric biosensor chip; Creatinine; Biosensor; Creatininase immobilization; Solid-state biosensor; ENZYME ELECTRODE; UREA; SYSTEM; SERUM; FILM; PH; Biotechnology & Applied Microbiology; Engineering